Effect of vitamin D on all-cause mortality in heart failure (EVITA): a 3-year randomized clinical trial with 4000 IU vitamin D daily. (12th May 2017) - Zittermann, Armin; Ernst, Jana B.; Prokop, Sylvana; Fuchs, Uwe; Dreier, Jens; Kuhn, Joachim; Knabbe, Cornelius; Birschmann, Ingvild; Schulz, Uwe; Berthold, Heiner K.; Pilz, Stefan; Gouni-Berthold, Ioanna; et al.
Abstract: Aims: Circulating 25-hydroxyvitamin D (25OHD) levels <75 nmol/L are associated with a nonlinear increase in mortality risk. Such 25OHD levels are common in heart failure (HF). We therefore examined whether oral vitamin D supplementation reduces mortality in patients with advanced HF. Methods and results: Four hundred HF patients with 25OHD levels <75 nmol/L were randomized to receive 4000 IU vitamin D daily or matching placebo for 3 years. Primary endpoint was all-cause mortality. Key secondary outcome measures included hospitalization, resuscitation, mechanical circulatory support (MCS) implant, high urgent listing for heart transplantation, heart transplantation, and hypercalcaemia. Initial 25OHD levels were on average <40 nmol/L, remained around 40 nmol/L in patients assigned to placebo and plateaued around 100 nmol/L in patients assigned to vitamin D. Mortality was not different in patients receiving vitamin D (19.6%; n  = 39) or placebo (17.9%; n  = 36) with a hazard ratio (HR) of 1.09 [95% confidence interval (CI): 0.69–1.71; P  = 0.726]. The need for MCS implant was however greater in patients assigned to vitamin D (15.4%, n  = 28) vs. placebo [9.0%, n  = 15; HR: 1.96 (95% CI: 1.04–3.66); P  = 0.031]. Other secondary clinical endpoints were similar between groups. The incidence of hypercalcaemia was 6.2% ( n  = 10) and 3.1% ( n  = 5) in patients receiving vitamin D or placebo ( P  = 0.192). Conclusion: A daily vitamin D dose of 4000 IU did not reduce mortality in patients with advanced HF but was associated with a greater need for MCS implants. Data indicate caution regarding long-term supplementation with moderately high vitamin D doses. Trial Registration Information: clinicaltrials.gov Idenitfier: NCT01326650.